The Effect of Macroeconomic Factors on The Financial Performance of Banking in Indonesia - Iqbal Firdausi (LAFADZ JAYA Publisher, 2022)
This study aims to determine the effect of short-term and long-term macroeconomic factors on the financial performance of Islamic banking in Indonesia. The dependent variables in this study are Return on Assets (ROA), Financial to Deposit Ratio (FDR) and Operating Costs of Operating Income (BOPO) as proxies of financial performance. While the independent variables are industrial production index (IPI), inflation, BI rate, composite stock price index (CSPI) and exchange rates. The analytical method used is Vector Error Correction Models (VECM). The data used in this study are monthly time series data from January 2010 - December 2015. The results of the study state that in the long term the influence of the Industrial Production Index (IPI), inflation and exchange rates have a negative and significant effect on Return on Assets ( ROA) and Financial to Deposit Ratio (FDR). Meanwhile, the BI rate and the Composite Stock Price Index (JCI) have a positive and significant impact on Return on Assets (ROA) and Financial to Deposit Ratio (FDR). Industrial Production Index (IPI), inflation and exchange rates have a positive and significant influence on the Operating Cost of Operating Income (BOPO). Meanwhile, the BI rate and the Composite Stock Price Index (JCI) have a negative and significant effect on the Operating Cost of Operating Income (BOPO). The short-term effect of macroeconomic variables on financial performance (ROA, FDR and BOPO) does not show a significant relationship.